Choledochoplasty with Gallbladder Wall Free Flap: A Novel Technique for Large Bile Duct Defects from Mirizzi Syndrome in High-Risk Patients—A Case Report and Literature Review. (30th July 2019) - Chai, Louis F.; Xiao, Gary S.
Abstract : Background. Cholecystectomies are almost universally performed laparoscopically with complication rates similar to open surgery. Possible complications include bleeding and damage to surrounding structures. These often require intervention to repair the damage immediately when recognized intraoperatively or postoperatively. These injuries can cause significant morbidity and mortality, and additional interventions further compound this, especially for high-risk patients. All attempts should be made to a lower risk while performing the safest operation and addressing complications appropriately. We present a case of a surgically high-risk patient who underwent an attempted laparoscopic, converted to open, cholecystectomy for Mirizzi syndrome, during which a biliary defect was found and repaired with a novel technique of choledochoplasty with a gallbladder wall free flap. Case . An 82-year-old female with abdominal pain was diagnosed with a cholecystocholedochal fistula from chronic cholecystitis and Mirizzi syndrome. During cholecystectomy, a large common bile duct defect was noted, and given intraoperative instability, the repair was completed using a gallbladder wall free flap. Postoperatively, the patient recovered well through a 4.5-year follow-up. Conclusion . Complications from laparoscopic cholecystectomy are rare but may result in additional interventions. For patients who are high-risk surgical candidates, gallbladder wall free flap choledochoplasty should be considered to avoid additional morbidity and mortality.